Instrument for Measuring Attitudes Toward Anemia Prevention Efforts in Pregnant Women - Karlina, Lini; Brian Sri Prahastuti; Nur Asni Djaali (LPPM Universitas Mohammad Husni Thamrin, 2025)
Anemia in pregnant women is a global health problem, with a prevalence reaching 48.9% in Indonesia according to the 2021 Basic Health Research (Riskesdas), which significantly impacts both the mother and the fetus. Positive attitudes toward anemia prevention have been shown to increase adherence to iron supplementation, but valid and reliable instruments for measuring attitudes are still limited. This study aims to develop a theory-based and psychometric-based instrument for measuring attitudes toward anemia prevention in pregnant women. The study employed a Research and Development (R&D) approach with 30 pregnant women in the PMB (PMB) area of ​​Bekasi, using a 60-item questionnaire with a 4-point Likert scale. Validity was tested using Pearson Product Moment correlation and reliability using Cronbach's Alpha. The results showed that all 60 items were valid with a correlation coefficient of 0.379–0.818 (r table = 0.361) and very high reliability (α = 0.959). The instrument consists of six dimensions: understanding, seriousness of the problem, threat, preventive behavior, healthy hygiene behavior, and anemia management. Pregnant women's attitudes are a form of internal evaluation that reflects knowledge, feelings, and behavioral tendencies towards various aspects of pregnancy, including anemia prevention efforts. This attitude is formed from personal experiences, information obtained, and the influence of the social environment such as family and health workers. Further research recommendations include validation on larger samples and implementation as a screening tool in maternal health programs to increase the effectiveness of anemia prevention.